Cellular and molecular mechanisms of calcific aortic valve disease - E. V. Shcheglova; M. Kh. Baykulova; O. I. Boeva (Российский кардиологический журнал, 2019)
The review provides current data on the pathogenesis of calcific aortic valve disease (CAVD) — a widespread disease with unfavorable prognosis. Currently, there are no effective therapeutic methods for the prevention and treatment of this pathology with the exception of valve replacement surgery. The role of genetic and hereditary factors in the occurrence of CAVD is considered, the leading pathogenetic mechanisms are described taking into account the stage of the disease. In particular, in the initiation phase of calcification, deposition of oxidized lipoproteins in the cusps and local inflammation plays the leading role. In the progression phase, active ectopic calcification dominates, similar to the process of bone formation. The study of the pathogenesis of CAVD seems appropriate taking into account the prospect of developing new effective therapeutic and prophylactic approaches.